Effect of soil mixing with silicon on growth, yield components and yield of maize under drought stress - Zahir, Abdul Rahman; Datta, Avishek; Soni, Peeyush; Kuwornu, John K.M.; AFG Western Basins Water Resources Management Project; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
An experiment was conducted during Nov 2016 to Mar 2017 at the greenhouse of Asian Institute of Technology, Thailand. The present research was designed as complete randomized design (CRD) and applied six different rates of Si (0, 18.75, 37.5, 75, 150 and 300 mg/kg) with three replications under three soil moisture levels (100 % FC, 75 % FC and 50 % FC). In this investigation evaluated the impact of soil mixing with Si on growth, yield components and grain yield of maize hybrid CP 888 New (drought sensitive) under drought stress. In this study, the severe drought stress (50 % FC) significant reduced growth attributes such as leaf area, plant height and number of leaf as compared to well-watered condition (100 % FC). Si applications significantly increased all growth parameters at vegetative stage under three soil moisture levels. Therefore, in this stage Si application and soil moisture regimes had not significant effect on chlorophyll content. At reproductive stage, severe drought stress significantly decreased all growth parameters and yield attributes such as plant height, leaf area, number of leaf, chlorophyll content, stem diameter, root dry weight, shoot dry weight, cob length, number of grain per ear, 100-grain yield and grain yield as compared to well-watered condition and 75 % FC. Si applications significantly improved all growth parameters, yield components and grain yield except chlorophyll content, root dry weight and shoot dry weight at reproductive stage under different soil moisture regimes.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Corn -- Effect of drought on; Soil moisture; Corn -- Planting